Police organization and the policing of assemblies in the United States - Hanson, Alan (Public Order Policing, 2024)
In this chapter, we highlight some aspects of the US police organization and standards that matter when policing assemblies or large-scale events. Hereafter, we will show an example of how an assembly would be policed using a fictitious case study in a fictitious city. At various points, we will also shed light on cross-border police collaboration in the United States.